T3SS mediated transcriptional reprogramming of rice by the virulent Indian race 4 of Xanthomonas oryzae pv. oryzae - M, Amrutha Lakshmi; Mondal, Kalyan K; NS, Kalaivanan (ORYZA-An International Journal of Rice, 2023)
Bacterial blight (BB) incited by Xanthomonas oryzae pv. oryzae (Xoo) is a constant threat to global rice production. Xoo attenuates host defense by directly translocating type III effectors (T3Es) into rice cytosol. The fleeting emergence of new virulent Xoo isolates and subsequent breakdown of resistance in the realm of an erratic climate entails the exploration of befitted resistance to prevent super-races of Xoo from becoming widespread. A comprehensive knowledge of T3Es-mediated transcriptional reprogramming of rice genes in response to Xoo infection remains elusive. Evidently, RNA seq-based transcriptome profiling of rice infected with an Indian virulent Xoo strain Race 4 relative to its T3SS-defective mutant strain (Xoo DhrpX) at early and late hours of bacterial infection yielded an array of differentially expressed genes (DEGs), 49 genes of which were selected for RT-qPCR analysis. The results revealed T3SS-dependent novel defence-related genes belonging to Nucleotide-binding leucine-rich repeat (NLRs), Receptor-like kinases (RLKs), PR proteins, enzymes, cytochrome P450 and secondary metabolites. These genes are direct targets for enhancing BB resistance as well silencing of susceptible targets through gene editing yields durable resistance.